Sureśa viśe viśesha : pustaka-prastāvanā-rūpe pragaṭa thayelā Sureśa Dalālanā vyakticitro = Suresh vishe vishesh : pen-sketches of Suresh Dalal written in form of prefaces to his books by various authors. (Mumbaī ane Amadāvāda : Īmeja Pablikeśansa, 2013)
Comlpilation of writings on Sureśa Dalāla, 1932-2012, written in form of prefaces to his books by various Gujarati authors.
In Gujarati.
Keywords: Dalāla, Sureśa Purushottamadāsa, -- 1932-2012 -- Criticism and interpretation; Dalāla, Sureśa Purushottamadāsa, -- 1932-2012.; Criticism, interpretation, etc